The green glass sea - Klages, Ellen 1954- (New York : Penguin Group, 2006)
"In 1943, eleven-year-old Dewey Kerrigan travels west on a train to live with her scientist father--but no one will tell her exactly where he is. When she reaches Los Alamos, New Mexico, she learns why: he's working on a top secret government program"--
M
Sequel: White Sands, red menace.
790
M
Keywords: Atomic bomb -- Fiction; Fathers and daughters -- Fiction; Scientists -- Fiction; Friendship -- Fiction; People with disabilities -- Fiction; World War, 1939-1945 -- United States -- Fiction